Budget impact of netupitant/palonosetron for the prevention of chemotherapy-induced nausea and vomiting. (3rd August 2019) - Park, Sang Hee; Binder, Gary; Corman, Shelby; Botteman, Marc
Abstract: Background: Chemotherapy-induced nausea and vomiting (CINV) are among the most common and debilitating side-effects patients experience during chemotherapy, and are associated with considerable acute care use and healthcare cost. It is estimated that 70–80% of CINV could be prevented through appropriate use of CINV prophylaxis; however, suboptimal CINV compliance and control remains an issue in clinical practice. Netupitant/palonosetron (NEPA) is a fixed combination of serotonin-3 (5-HT3 ) and neurokinin-1 (NK1 ) receptor antagonists (RAs), respectively, indicated for the prevention of acute and delayed nausea and vomiting associated with highly emetogenic chemotherapy (HEC) and moderately emetogenic chemotherapy (MEC). Phase 3 clinical trials showed a significantly higher complete response rate in both acute and delayed CINV in chemotherapy-naïve patients receiving NEPA compared to patients receiving palonosetron. Objective: The objective of this study was to estimate the budgetary impact of adding NEPA to a US payer or practice formulary for CINV prophylaxis. Methods: A model was developed to estimate the impact of adding NEPA to the formulary of a hypothetical US payer with 1.15 million members, including 150, 000 (13%) Medicare beneficiaries. The model compared the annual total costs of CINV-related events and CINV prophylaxis in two scenarios: base year (no NEPA) and comparator year (10% and 5% NEPA usage in HEC and MEC patients, respectively). A univariate sensitivity analysis was conducted to explore the effect of variability in model parameters on the budget impact. Results: A total of 2, 021 patients were eligible to receive CINV prophylaxis. With NEPA, CINV prophylaxis costs increased by 0.7% ($3, 493, 630 vs $3, 518, 760) while medical costs associated with CINV events decreased by 3.9% ($15, 118, 639 vs $14, 532, 442), resulting in a net cost saving of $561, 067 (3.0%) for the health plan ($18, 612, 269 vs $18, 051, 202), or $0.04 per member per month. This was equivalent to saving $5, 011 per patient moved to NEPA. Among all 5-HT3 RA + NK1 RA regimens, NEPA was associated with the lowest CINV-related costs, leading to the lowest total cost of care. Conclusions: Adding NEPA to a payer or practice formulary results in a net decrease in the total budget due to a substantial reduction in CINV event-related resource utilization and medical costs, and an increase in pharmacy costs <1%, saving over $5, 000 per patient.